1996
DOI: 10.1111/j.1439-0507.1996.tb00099.x
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of pityriasis versicolor in Malawi, Africa

Abstract: During a total population survey in 1988 and 1989 in Karonga district, northern Malawi, 4915/61735 (8.0%) people examined were found to have extensive pityriasis versicolor (PV). An additional 6085 people (9.9%) were diagnosed as having mild disease. The highest prevalence rates of extensive and mild PV were found among subjects aged 15-24 years. In this age group between 20% and 25% of people had extensive PV. Rates were generally higher among males than among females. PV was rarely found in prepubertal subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 7 publications
(1 reference statement)
4
9
0
Order By: Relevance
“…This study therefore provided an update that skin conditions were still a major public health problem affecting 18% of the population aged 5 years or more. Our findings that fungal infections, pityriasis versicolor in particular being the commonest skin infections were consistent with previous findings [21]. Previous trials indicated that Whitfield's and clotrimazole creams were effective for the treatment of common fungal skin infections in Malawi with cure rates of 80%-90%.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This study therefore provided an update that skin conditions were still a major public health problem affecting 18% of the population aged 5 years or more. Our findings that fungal infections, pityriasis versicolor in particular being the commonest skin infections were consistent with previous findings [21]. Previous trials indicated that Whitfield's and clotrimazole creams were effective for the treatment of common fungal skin infections in Malawi with cure rates of 80%-90%.…”
Section: Discussionsupporting
confidence: 92%
“…Recent population-based prevalence estimates of skin conditions are not well documented in Malawi except 1980s data from Karonga [21,22]. This study therefore provided an update that skin conditions were still a major public health problem affecting 18% of the population aged 5 years or more.…”
Section: Discussionmentioning
confidence: 91%
“…Pityriasis versicolor is a common finding in Ethiopia (13.6% of the total cases of superficial fungal infection). This finding correlates with similar findings in Malawi: 8% of the study group had extensive pityriasis versicolor, while 9.9% had a mild form of pityriasis versicolor 10 . Pityriasis versicolor is caused by a normal flora of the human skin ( Malassezia furfur ).…”
Section: Discussionsupporting
confidence: 90%
“…Relatively higher rate of T. versicolor (7.7%) was reported in hospital based study in Cairo (14). In Northern Malawi, much higher rate (17.9%) was observed among the total population (22).The difference in the prevalence rates of T. versicolor among different surveys has been devoted mainly to individual susceptibility. In addition, environmental factors may play a role with higher prevalence rate in tropical climate than in temperate one.…”
Section: Infective Skin Diseasesmentioning
confidence: 93%